PERAN UNI EROPA DALAM PROSES PENYELESAIAN SENGKETA BAGI NEGARA ANGGOTA DAN NEGARA NON ANGGOTA - Carina Etta Siahaan; Arif Arif; Deni Purba (Journal of USU International Law, 2013)
Abstract The main reason for the establishment of the first European Union once was because of the desire to provide protection to the European countries that are victims of cruel regimes of Germany during World War II. After the signing of the Maastricht Treaty in 1992, the European Union is increasingly proving its progress to the international community as one of the largest regional organizations. Expand the authority of the European Union in the field of law to be the same as the state. The European Union has a great sovereignty of the member states. Help resolve internal disputes in the European Union has two methods to resolve the internal disputes through alternative and legal means. The purpose of this paper is to look at the mechanism by the European Union as an international organization in its role to resolve disputes in the European Union. As an International Organisation which aims at maintaining world peace and security, the European Union also play the role to help resolve disputes outside the European Union. With the development of increasingly advanced, the European Union as an international organization has the effect of maintaining security and peace in the world, because it is also the European Union, have the opportunity to be able to play non-member countries to resolve disputes, without passing the limits of the sovereignty of a non-member country. Keyword: European Union, Dispute Resolution, Member States and non-State Member.